The Using Natural Phenomenon Video In The Science Learning On Junior High School Student’s Scientific Creativity - Aninnas, Afina; Supeno, Supeno; Wicaksono, Iwan (Phenomenon : Jurnal Pendidikan MIPA, 2022)
Tujuan penelitian ini adalah mengkaji pengaruh dan peningkatan pemanfaatan video fenomena alam terhadap kreativitas ilmiah siswa. Penelitian eksperimen ini menggunakan desain penelitian eksperimen quasi dengan rancangan nonequivalent control-group design. Instrumen penelitian berupa tes kreativitas ilmiah yang hasilnya dianalisis menggunakan uji N-Gain dan independent sample t-test. Berdasarkan hasil uji N-Gain, diperoleh peningkatan kreativitas ilmiah pada kelas eksperimen dalam kategori sedang dan pada kelas kontrol dalam kategori rendah. Hasil uji hipotesis menunjukkan perbedaan nilai yang signifikan antara kelas control dan eksperimen. Kesimpulan yang dapat diambil bahwa pemanfaatan video fenomena alam dalam pembelajaran IPA materi lapisan bumi dapat meningkatkan kreativitas ilmiah siswa dalam kategori sedang serta berpengaruh signifikan terhadap kreativitas ilmiah siswa MTsAbstract The purpose of this study was to examine the effect and increase in the use of videos of natural phenomena on students' scientific innovation. This experimental study used a quasi-experimental research design with a nonequivalent control-group design. The research instrument was a scientific creativity test, the results of which were analyzed using the N-Gain test and independent sample t-test. Based on the results of the N-Gain test, there was an increase in scientific creativity in the experimental class in the medium category and in the control class in the low category. The results of the hypothesis test showed a significant difference in values between the control and experimental classes. The conclusion that can be drawn is that the use of videos of natural phenomena in natural science learning for earth layer material can increase students' scientific creativity in the medium category, which has a significant effect on scientific innovation of junior high school students.